Java Structures : Data Structures in Java for the Principled Programmer - Bailey, Duane A. (Boston : Mc Graw Hill, 2003)
Considers the design, implementation, and use of data structures using Java 2. This is a collection of nearly 100 different classes, implementing a variety of data structures. It is suitable for faculty, students, researchers, and industrial and recreational programmers. It aims to provide the programmer choices of data structure
Keywords: Java (Computer Program Ianguage); Data Structures (Computer Science); Java (programmeringssprog); programmeringssprog; programmering